IMPACT OF ONLINE LEARNING AND ACADEMIC ENGAGEMENT OF STUDENTS - Patwa, Chandra Kant; Srivastava, Vartika; Kavita Verma (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In view of the global pandemic COVID-19, online learning was implemented in most education systems around the world. In the current situation, online education was found to be highly effective for students. However, the reality of online education is that it is extremely challenging for students of all other educational institutions including universities. While online education, on the one hand, manages physical distance and time in learning rapidly, on the other hand, it also creates various types of technical and communication related problems. The lesser the physical distance between the teacher and the student, the more is the participation. If proper communication means are used between the teacher and the student in online education, so that the process of learning and teaching can be conducted properly, then the participation of students in the teaching process can be increased. Due to the absence of educational and psychological environment in the process of online learning, many students are only physically present in the class, due to which there are many obstacles in their learning, which affects the participation of students in class teaching.